1986
DOI: 10.1111/j.1751-0813.1986.tb08069.x
|View full text |Cite
|
Sign up to set email alerts
|

Encephalomyocarditis virus disease of pigs associated with a plague of rodents

Abstract: An epizootic of encephalomyocarditis virus (EMCV) disease in pigs in the central west of New South Wales in association with a plague of mice (Mus musculus) in 1984 is described. The disease was confirmed in 47 outbreaks in 37 piggeries and 1152 pigs died, representing an overall death rate of 17.4% in pigs considered at risk. The disease was diagnosed in both intensively housed pigs and pigs farmed outdoors, with mortality rates higher in piggeries with less than 50 sows. The age at which pigs died ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 2 publications
(8 reference statements)
4
32
0
Order By: Relevance
“…It is ubiquitous in nature and has been isolated from both animals (insects, birds, mammals) and humans [35,40]. Several studies indicate that EMCV can cause interspecies infections, making it a potential zoonotic agent [5,13,16,28,30]. However, most of the evidence of human infection has been indirect, detected from the presence of antibodies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is ubiquitous in nature and has been isolated from both animals (insects, birds, mammals) and humans [35,40]. Several studies indicate that EMCV can cause interspecies infections, making it a potential zoonotic agent [5,13,16,28,30]. However, most of the evidence of human infection has been indirect, detected from the presence of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates that have caused myocarditis in pigs have been associated with rodent outbreaks [2,19,30]. In wild rodents, the natural hosts, the virus usually persists without causing disease [32], whereas infection in laboratory rodents commonly [30] produces fatal encephalitis or myocarditis [7,9,23,27,33,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutralising antibodies can be detected as early as 5 days postinoculation in experimentally infected pigs [1], whereas the virus can be isolated from blood and excreta already one day after inoculation [3,7,17]. EMCV-transmission has been described from rodents to a wide variety of other species, including humans [1,16,22], while a recent study indicated that rats easily spread the virus among each other [24]. Although EMCV-transmission from rodents to pigs is considered important, also the impact of horizontal and vertical pig-to-pig transmission needs to be known/quantified to understand their contribution to the spread of the disease on a pig farm [7,17].…”
Section: Introductionmentioning
confidence: 99%
“…At first, pigs might get infected by the ingestion of substances (e.g. faeces or carcasses) of infected rodents [1,20,23]. The second route is horizontal pig-to-pig transmission during the short period of viraemia [4,17] or after reactivation of EMCV persistence [5].…”
Section: Introductionmentioning
confidence: 99%